Refugees emergency and bioethical issues - Schiavone, Valeria (Medicina Historica, 2023)
Migratory movements and their policies represent one of the greatest challenges to our European societies. Bioethics can and must question respect for the lives of the thousands of people who have a migration project, as a common aspiration of all living beings to imagine and realise different and better living conditions.